Western Kazakhstan as One of the Centers of the Ulus of Jochi in the XIII–XIV Centuries - Bisembaev Arman A.; Akhatov Gaziz A.; Khavansky Alexey I. (Поволжская археология)
The article is devoted to the latest research of monuments of the Ulus of Jochi period in the territory of Western Kazakhstan. The study of monuments of the developed and late Middle Ages was carried out in three main directions – processing and analysis of available materials, obtained as a result of research on the territory of the region from the second half of the XIX century to the present time, conducting exploration activities to identify the most promising areas of the location of Golden Horde monuments and reconnaissance excavations. The survey of the Uil-Kobda local microdistrict was associated with the study of a large necropolis and settlement of Koptam, neighbourhood of the Abat Baytak cult mausoleum. Kyzyltam mausoleum, located on the Kargaly reservoir shore, was also a marker of the center of a large nomadic group in the Late Middle Ages. The stages of gradual adoption of Islam by the population are clearly visible on the monuments of the Ulus of Jochi, when the burial rites undergo "standardization", and the sets of inventory show the spread of a common fashion, the so-called "imperial" style. The forced migration policy of the Mongolian khans is visible on the burial monuments, and there are objects associated with the Southern Siberia population.